The Effectiveness of Exercise in Adults With Systemic Lupus Erythematosus: A Systematic Review and Meta‐Analysis to Guide Evidence‐Based Practice. Issue 4 (22nd April 2017) - Wu, Mei‐Ling; Yu, Kuang‐Hui; Tsai, Jen‐Chen
ABSTRACT: Background: Fatigue is the most common and unpleasant symptom of patients with systemic lupus erythematosus (SLE). However, there is limited information regarding how exercise affects fatigue. Aims: The purpose of this study is to review and synthesize the current knowledge concerning the effectiveness of exercise training for treating fatigue among adults with SLE. The characteristics of beneficial exercise training are further evaluated. Methods: We conducted a systematic review and meta‐analysis. The databases searched were MEDLINE, CINAHL, PEDro, Cochrane Library, Scopus, and PQDT from their inception to February 3, 2016. The quality of each selected study was assessed using the PEDro scale. A between‐group analysis was performed to evaluate the effectiveness of the exercise training. Data were analyzed using the Cochrane Collaboration's RevMan 5.3 (Copenhagen, Denmark). Results: Two randomized controlled trials and one quasiexperimental study were included in this systematic review and meta‐analysis. Aerobic exercise, three times a week and of moderate intensity, was a common component of the three studies. Two studies were conducted in a supervised setting and one study was based at home. One study lasted 8 weeks and two studies lasted 12 weeks. The meta‐analysis showed that aerobic exercise could decrease fatigue (MD = –.52, 95% confidence interval [CI] [–.91, –.13], p = .009) and increase vitality (MD = 14.98, 95% CI [7.45, 22.52], p < .001). The subgroup analysis indicated that 12 weeks of exercise training and exercise under a supervised setting significantly benefited fatigue. Linking Evidence to Action: The pooled data indicate that 12 weeks of an aerobic exercise program that is supervised by health professionals could reduce fatigue and increase vitality for patients with SLE. SLE patients with mild disease should begin with moderate intensity for at least 20 minutes, 3 days a week.